Karakteristik Permen Keras (Hard Candy) Wortel dan Lemon - Intan Kusumaningrum (JURNAL AGROINDUSTRI HALAL, 2019)
Carrot is one of vagatable that contains plenty of nutritions and as the source of ß-carotene. Lemon is one of fruit that contains plenty of nutritions and as the source of Vitamin C. Both of carrot and lemon have a lot of nutritional content for human body, but still has very limited utilization. Product innovation for carrot and lemon is needed in order to give diverse utilization of carrot and lemon. Hard candy is a product that contains sucrose, glucose, water as the main raw materials, and has hard, transparant, glossy texture. Making hard candy that contain carrot and lemon is one of ways to utilize carrot and lemon and give beneficial nutritions to human body. This study aims to find preffered formulation to make carrot and lemon hard candy. This hard candy is made with three ratio comparation sucrose and glucose that calculated in grams (75:25, 70:30, 65:25), and two comparation on time of cooking (5mins and 7mins). The analysis performed included organoleptic (quality of sensory and hedonic test), content of chemistry test, such as moisture content, ash, vitamin C, invert sugar, and ß-carotene. The selected hard candy of carrot and lemon is A1 (75:25) B1 (5mins), with moisture content 1,31%, ash 0,145%, invert sugar 44%, vitamin C 0,835%, and ß-carotene 0,675%. Keywords : hard candy, carrot, lemon.